Enhancing consumer loyalty through Islamic experience-based marketing in legendary culinary businesses - Dayu, Wulan; Ramadhan, Muhammad; Julianti, Yenni Samri; Razali, Hasrul Affendi Bin Mohmad (LPPM ISNJ Bengkalis, 2025)
Purpose – This study examines the impact of the Islamic experiential marketing strategy and value co-creation on customer loyalty, considering customer satisfaction as a mediating variable. This study develops a model integrating subjectivist spirituality within Islamic marketing to improve consumer experiences and loyalty. Method – This study utilizes a quantitative method, analyzing survey data obtained from 265 consumers of renowned culinary establishments in Medan city, where the sample was selected using a purposive sampling method. Data was analyzed using structural equation modeling (SEM) to investigate the relationship between variables and the research instruments underwent validation and reliability tests. Findings – The findings show that Islamic experiential marketing strategy positively affects customer satisfaction. Islamic experiential marketing strategy negatively affects customer loyalty. Value co-creation negatively affects customer satisfaction. Value co-creation positively affects customer loyalty. Customer satisfaction positively affects customer loyalty. Customer satisfaction can mediate the relationship between Islamic experiential marketing strategy and value co-creation with loyalty. Implications – This study can extend the existing literature on Islamic marketing by integrating subjectivist spirituality, thereby enhancing understanding of the factors that drive consumer loyalty. These findings are of practical importance to culinary businesses looking to increase consumer engagement and retention by integrating Islamic values ​​into experiential marketing strategies and co-creation, enabling businesses to foster lasting consumer relationships while upholding Islamic marketing practices.